Inflammation and obesity : a new and novel approach to manage obesity and its consequences - Mehrzad, Raman (Academic Press, 2022)
Inflammation and Obesity: A New and Novel Approach to Manage Obesity and its Consequences is a comprehensive and up-to-date exploration of the correlation between obesity and inflammation. From the pathophysiology of obesity and inflammation, to the molecular mechanisms of obesity induced chronic inflammation, the book discusses how obesity and inflammation interact with other diseases. It highlights the hidden risk factors of obesity induced chronic inflammation, provides specific patient management guidelines regarding the higher inflammatory response in patients, and concludes with new therapeutic strategies to address inflammation in obese patients.